Ο βυζαντινός στρατός των Αγγέλων, μέσα από τις περιγραφές των λατίνων αντιπάλων του - ΑΛΕΞΟΠΟΥΛΟΣ Θεοχάρης (Byzantina Symmeikta, 2019)
The Byzantine Army of the Period of the Angeli, according to the Accounts of the Latin Sources There is hardly any information available about the byzantine army under the dynasty of Angeli, about its numbers, composition and performance in battle. With the exception of Choniates no other byzantine gives any useful information. Under this prism the western European sources of the third and fourth crusades could provide valuable information, if properly read. Chronicles such as Historia de expeditione Friderici imperatoris and the Historia Peregrinorum from Germany and the Itinerarium peregrinorum and the Estoire de la guerre sainte of Ambroise from England together with the famous and much read chronicles of Robert Clari and Geoffroi Villehardοuin from France give a very different account than usual about the true capabilities of the byzantine army on the eve of the fourth crusade. The information derived from these sources picture a very grim situation for the byzantine state in general. The army was greatly outnumbered by its foes, without capable leadership and enough reserves to defend even the capital. Nevertheless, when properly handled it could still be a dangerous opponent for the superior crusader armies.